Prognostic Value of Matrix Metalloproteinase 9 (MMP9) in Patients Following Off-Pump Coronary Artery Bypass Grafting - Mikhail Popov; Siarhei Dabravolski; Vladislav Dontsov; Sergei Vzvarov; Evgeniy Agafonov; Dmitriy Zybin; Olga Radchenkova; Dmitriy Saveliev; Victoria Pronina; Natalia Kashirina; Liudmila Lipatova; Mikhail Peklo; et al. (Life, 2025)
Background: Matrix metalloproteinase 9 (MMP9) has recently emerged as a risk predictor in patients with cardiovascular diseases (CVD). However, little is known regarding the significance of elevated plasma MMP9 levels in patients during the long-term period following myocardial revascularisation. We aimed to investigate the role of MMP9 in relation to myocardial status before and after myocardial revascularisation and to assess its long-term prognostic value. Methods: This prospective observational study included 200 male patients with ischaemic heart disease. All patients underwent direct myocardial revascularisation on a beating heart (off-pump surgery). Plasma MMP9 levels were analysed preoperatively, at 48 h postoperatively, and during the long-term follow-up period (one year postoperatively). Key echocardiographic parameters, specifically left ventricular ejection fraction (LVEF) and Left Ventricular End-Diastolic Volume (LVEDV), were also assessed. Results: MMP9 levels decreased significantly at 48 h postoperatively (p < 0.0001). During the long-term postoperative period, a clear relationship was demonstrated: higher 1-year MMP9 levels were associated with lower 1-year LVEF, whilst lower 1-year MMP9 levels were associated with higher 1-year LVEF. No significant correlation was observed between preoperative MMP9 levels and age or most other baseline laboratory parameters. Conclusions: Our study established an association between 1-year postoperative MMP9 levels and key parameters of left ventricular function during the long-term follow-up period. This suggests that MMP9 may serve as a novel biomarker for predicting outcomes following myocardial revascularisation.